Gas companies in the electricity sector in Spain and France, between late 19th Century and early 20th Century - Fernández-Paradas, Mercedes; Larrinaga Rodríguez, Carlos; Pinto Tortosa, Antonio Jesús (My University, 2022)
Since late-19th Century, gas companies faced the competition of electricity produced at an industrial scale. It was then necessary to think of different strategies. State governments and municipal administrations were against monopolistic property by gas companies. The latter started lawsuits to avoid the entrance of electricity companies into the energy market. They started technological innovations to improve the quality of the gas produced and to low its cost down. Moreover, advertising campaigns were designed in order to attract new clients and increase gas consume, above all in lighting. At the same time, they carried out a company concentration process, and most of them decided to participate in the electricity sector, too. That is, they tried to stop new electric companies from entering the energy market by devoting themselves to electricity production, a strategy that deserves all the attention of the historiography about the gas industry. In this paper, we aim at studying the issue for the first time in Spain and France, since the 1890s till the 1920s.
Keywords: Compañias de gas; Energía eléctrica -- distribución -- España -- Historia; Energía eléctrica -- distribución -- Francia -- Historia; Gas; Electricidad; Competencia; España; Francia; Siglo XIX; Siglo XX